Global perspectives in acute and emergency general surgery in low and middle-income countries: a WSES project protocol for scoping review on global surgery - Mahmoud Diaa Hindawi; Arda Isik; Fausto Rosa; Diego Visconti; Taras Nechay; Sharfuddin Chowdhury; Abdourahmane Ndong; Tushar S. Mishra; Stefano Piero Bernardo Cioffi; Francesco Piscioneri; Edward C.T.H. Tan (World Journal of Emergency Surgery)
Abstract Background Around five billion people globally lack access to safe, timely, and affordable surgical facilities and care in low-income and middle-income countries (LMICs). Global initiatives have been launched, including efforts led by organizations. Also, regional efforts have shed light on the unique challenges faced by different areas within LMICs. Despite these efforts, many countries still face significant challenges, including inadequate infrastructure, limited availability of trained surgical personnel, lack of essential medical equipment, and insufficient financial resources allocated to healthcare and their related possible factors. Here is that we aim to identify the progress made in areas such as capacity building, training programs, infrastructure development, and policy reforms, as well as highlight the gaps that persist, providing a foundation for future research. Such a comprehensive scoping review will be crucial to enhance surgical care services and ultimately improve health outcomes in LMICs. Methods A comprehensive literature search up to November 2024 will be conducted across six major databases. PubMed, Scopus, Ovoid, Web of Science, Cochrane Central, CNKI (China National Knowledge Infrastructure) database. The methodology will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) Checklist. The first version of this project will not include a quality appraisal.